Conjugate electro-spinning towards Janus nanofibers array synchronously endowed with conductive anisotropy, magnetism and luminescence. (December 2022) - Qi, Haina; Wang, Guoyi; Hu, Yaolin; Shao, Hong; Ma, Qianli; Li, Dan; Yu, Wensheng; Chang, Limin; Zhang, Xuejian; Dong, Xiangting
Abstract: An unpolymerized [Tb(BA)3 phen (TBP)/polymethylmethacrylate (PMMA)]//[aniline (ANI)/Fe3 O4 /PMMA] Janus nanofibers array (UJNA) is successfully prepared by conjugate electro-spinning technique, and a polymerized [TBP/PMMA]//[polyaniline (PANI)/Fe3 O4 /PMMA] Janus nanofibers array (PJNA) with tunable conductive anisotropy, tailored magnetism and enhancive green luminescence is prepared by post-polymerization method. Using conjugate electro-spinning can prevent the problem of mutual diffusion between spinning dopes and realize the effective separation of luminescent substances form conductive-magnetic substances. Meanwhile, Janus nanofibers have a directional arrangement that can reduce light loss during excitation and emission. Therefore, compared with comparison samples, the PJNA prepared by conjugate electro-spinning has the strongest luminescence intensity. PJNA can be composed and contained different amounts of luminescent-conductive-magnetic (LCM) substances to adjust its LCM properties. As PANI mass ratio exceeds 70%, the sample's conductivity in the conductive direction exceeds that in the insulation direction by 10 7 times. The PJNA assembled in this work has potential applications in drug delivery, dual-mode imaging, electromagnetic shielding and nanodevices due to its excellent multifunctional properties. Further, this technology can also be applied to other multifunctional one-dimensional Janus nanomaterials and two-dimensional films. Graphical Abstract: ga1 Highlights: Janus nanofibers array is prepared by conjugate electrospinning and post-polymerization. Janus nanofibers (JNs) array owns conductive anisotropy, magnetism and luminescence. Conjugate electrospinning is superior to parallel electrospinning in making JNs. Partitioned structures guarantee strong luminescence and high conductive anisotropy. Other multifunctional nanomaterials can be constructed using these techniques.